2022
DOI: 10.3389/fcimb.2022.953392
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Microbial and Metabolomic Profiles in Kidney Stone Disease

Abstract: BackgroundKidney stones or nephrolithiasis is a chronic metabolic disease characterized by renal colic and hematuria. Currently, a pathogenetic mechanism resulting in kidney stone formation remains elusive. We performed a multi-omic study investigating urinary microbial compositions and metabolic alterations during nephrolithiasis.MethodUrine samples from healthy and individuals with nephrolithiasis were collected for 16S rRNA gene sequencing and liquid chromatography-mass spectroscopy. Microbiome and metabolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
1
14
0
2
Order By: Relevance
“…In parallel to the protective metabolites, several lines of evidence suggest that a number of amino acid metabolic pathways are closely related to the formation of kidney stone [4,[32][33][34]. Correspondingly, our research results manifest that serum cysteine is stimulative factors towards urolithiasis.…”
Section: Discussionsupporting
confidence: 67%
“…In parallel to the protective metabolites, several lines of evidence suggest that a number of amino acid metabolic pathways are closely related to the formation of kidney stone [4,[32][33][34]. Correspondingly, our research results manifest that serum cysteine is stimulative factors towards urolithiasis.…”
Section: Discussionsupporting
confidence: 67%
“…stones [39]. Regular monitoring of urinary parameters, including urine pH, calcium, and oxalate levels, can help identify at-risk individuals and enable early intervention.…”
Section: Plos Onementioning
confidence: 99%
“…Gao et al. proposed that E. coli, Staphylococcus , and Lactobacillus were strong predictors of renal calculi and first reported that Mycoplasma and Micrococcus were also involved in kidney stones, but their potential significance in kidney stones still needs to be studied in more detail ( 156 ).…”
Section: Other Metabolic Changesmentioning
confidence: 99%